If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18y + 11 = 15y + 17 Reorder the terms: 11 + 18y = 15y + 17 Reorder the terms: 11 + 18y = 17 + 15y Solving 11 + 18y = 17 + 15y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-15y' to each side of the equation. 11 + 18y + -15y = 17 + 15y + -15y Combine like terms: 18y + -15y = 3y 11 + 3y = 17 + 15y + -15y Combine like terms: 15y + -15y = 0 11 + 3y = 17 + 0 11 + 3y = 17 Add '-11' to each side of the equation. 11 + -11 + 3y = 17 + -11 Combine like terms: 11 + -11 = 0 0 + 3y = 17 + -11 3y = 17 + -11 Combine like terms: 17 + -11 = 6 3y = 6 Divide each side by '3'. y = 2 Simplifying y = 2
| 8(h-1)=64+4+2h | | 4y=50+2d | | 7c-4=10c+14 | | 120+x=x+70 | | y-5=-.5x-(-2) | | 14+9z+4+3z-z=51 | | p^2+5p-10=0 | | 7208-220x=0. | | 5p-5=-5p-65 | | 8g-3(7g+6)= | | 2p+7whenp=2 | | 320+80x=0. | | 6z+10=3 | | 2y+7+8y-37=20 | | y-3=4x-2 | | 2.5(x+2)+4.5+1.5(x+3)=15 | | 5(n-10)=125+2n | | 15=-5-15-8u | | -7w+4(w-5)=-38 | | y-3=-2x-9 | | 12t=10 | | 22-0.8q=6+1.2q | | 6000+5045x=5795x | | 10y+8y=153 | | y-6=-2x-(-3) | | 5y-3=2y-18 | | 27t^2-6t=0 | | 12d=10 | | 5(x+2)+8x=36 | | 33= | | 2200-q^2=400+q^2 | | 3/2-1/2=x |